INOVASI MANAJEMEN KEUANGAN MELALUI KEGIATAN KEWIRAUSAHAAN (EDUPRENEURSHIP) SEBAGAI UPAYA PENINGKATAN MUTU PEMBELAJARAN DI MI - Suhermi, Lulut; Salim, Muhlisin; Bambang, Bambang (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
Financial limitations are often the main obstacle in improving the quality of learning in Islamic Elementary Schools (MI). Funding from the government and parental contributions (SPP) are often insufficient to finance innovative infrastructure and learning programs. This study aims to analyze how financial management innovation through entrepreneurial activities (edupreneurship) can contribute to improving the quality of learning in MI. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, participant observation, and documentation studies at MI Al-Ikhlas as the research locus. Data were analyzed interactively through data reduction, data presentation, and drawing conclusions. The research findings show that: (1) The implementation of edupreneurship through the "Market Day" program, plant cultivation, and handicraft production has successfully created new sources of income for the madrasah. (2) The resulting funds are managed with an innovative, transparent, and accountable financial management system, including planning, budgeting, implementing, and reporting. (3) The proceeds from this financial management are allocated directly to support improvements in the quality of learning, such as purchasing science teaching aids, procuring literacy-supporting reading materials, and providing training to improve teacher competency. Edupreneurship-based financial management innovation has proven effective not only in increasing the financial independence of madrasas but also significantly impacting the quality of learning input, process, and output. This model can be an alternative solution for other Islamic elementary schools (MIs) to overcome funding constraints while instilling an entrepreneurial spirit in students. ABSTRAKKeterbatasan finansial seringkali menjadi kendala utama dalam peningkatan mutu pembelajaran di Madrasah Ibtidaiyah (MI). Pendanaan dari pemerintah dan iuran orang tua (SPP) seringkali belum mencukupi untuk membiayai sarana prasarana dan program pembelajaran yang inovatif. Penelitian ini bertujuan untuk menganalisis bagaimana inovasi manajemen keuangan melalui kegiatan kewirausahaan (edupreneurship) dapat berkontribusi terhadap peningkatan mutu pembelajaran di MI. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Teknik pengumpulan data dilakukan melalui wawancara mendalam, observasi partisipan, dan studi dokumentasi di MI Al-Ikhlas sebagai lokus penelitian. Data dianalisis secara interaktif melalui reduksi data, penyajian data, dan penarikan kesimpulan. Temuan penelitian menunjukkan bahwa: (1) Penerapan edupreneurship melalui program "Market Day", budidaya tanaman, dan produksi kerajinan tangan berhasil menciptakan sumber pendapatan baru bagi madrasah. (2) Dana yang dihasilkan dikelola dengan sistem manajemen keuangan yang inovatif, transparan, dan akuntabel, meliputi perencanaan (planning), penganggaran (budgeting), pelaksanaan (implementing), dan pelaporan (reporting). (3) Hasil dari pengelolaan keuangan ini dialokasikan secara langsung untuk mendukung peningkatan mutu pembelajaran, seperti pembelian alat peraga IPA, pengadaan buku bacaan penunjang literasi, dan pelatihan peningkatan kompetensi guru. Inovasi manajemen keuangan berbasis edupreneurship terbukti efektif tidak hanya dalam meningkatkan kemandirian finansial madrasah tetapi juga secara signifikan berdampak pada peningkatan kualitas input, proses, dan output pembelajaran. Model ini dapat menjadi alternatif solusi bagi MI-MI lain untuk mengatasi keterbatasan dana sekaligus menanamkan jiwa kewirausahaan kepada peserta didik.